An assessment of contaminants and benthic condition in the Matagorda Bay system (Texas, USA) - Jasmine J. Caillier; Paul A. Montagna; Marie E. DeLorenzo; Katy W. Chung; Peter B. Key (Environmental Science and Pollution Research, 2026)
The Matagorda Bay system has suffered a long-term decline in benthic abundance, biomass, and diversity since the 1980’s. This study examined sediment contamination to determine if legacy pollutants are degrading sediment quality and are a possible cause for ecosystem degradation. Degradation can be indicated by a decline in benthic integrity (i.e., diversity), decreased survival rates of organisms exposed to sediment, and sediment chemical contaminant concentrations over threshold limits. These methods form the Sediment Quality Triad to assess environmental effects. There were no contaminant concentrations above threshold limits for PCBs or DDTs, but 46% of 24 stations had concentrations over threshold limits, established by sediment quality guidelines, for seven trace elements and one PAH: arsenic (As), cadmium (Cd), mercury (Hg), copper (Cu), lead (Pb), nickel (Ni), and silver (Ag); and dibenzo (a,h) anthracene. Mostly near river mouths, 16 of the 24 stations had moderate to high toxicity, and 17 out of the 24 stations had fair to low diversity. Toxicity was inversely correlated with diversity, but there were no correlations between sediment chemistry and toxicity or benthic metrics. These findings indicate that legacy chemical contamination is not driving estuary-wide degradation of benthic communities The only station where high contamination was linked to high toxicity and low diversity was in the uppermost region of Lavaca Bay close to creek mouths. Low diversity and/or high toxicity was common near river and creek mouths. Because unmeasured pollution could be entering from rivers and creeks, management plans for the watershed and non-point sources could help to protect this ecosystem.

Evaluating the influence of high-resolution image capture on the signal strength of blue intensity and quantitative wood anatomy metrics from whitebark pine - Savannah A. Collins-Key; Maegen L. Rochner; Karen E. King; April L. Kaiser; Grant L. Harley; Zachary Foley; Matthew F. Bekker; Georg von Arx (Dendrochronologia, 2025)

Effects of Vibrio vulnificus and Microcystis aeruginosa co-exposures on microplastic accumulation and depuration in the Eastern Oyster (Crassostrea virginica) - Jessica T. Wenclawiak; John E. Weinstein; Peter B. Key; Craig J. Plante; Barbara A. Beckingham (Environmental Pollution, 2024)

Influence of colourants on environmental degradation of plastic litter - Sarah Key; Peter G. Ryan; Sarah E. Gabbott; Jack Allen; Andrew P. Abbott (Environmental Pollution, 2024)

Siderophore production and utilization by marine bacteria in the North Pacific Ocean - Jiwoon Park; Bryndan P. Durham; Rebecca S. Key; Ryan D. Groussman; Zinka Bartolek; Paulina Pinedo‐Gonzalez; Nicholas J. Hawco; Seth G. John; Michael C. G. Carlson; Debbie Lindell; Lauren W. Juranek; Sara Ferrón; et al. (Limnology and Oceanography, 2023)
Siderophores are strong iron‐binding molecules produced and utilized by microbes to acquire the limiting nutrient iron (Fe) from their surroundings. Despite their importance as a component of the iron‐binding ligand pool in seawater, data on the distribution of siderophores and the microbes that use them are limited. Here, we measured the concentrations and types of dissolved siderophores during two cruises in April 2016 and June 2017 that transited from the iron‐replete, low‐macronutrient North Pacific Subtropical Gyre through the North Pacific Transition Zone (NPTZ) to the iron‐deplete, high‐macronutrient North Pacific Subarctic Frontal Zone (SAFZ). Surface siderophore concentrations in 2017 were higher in the NPTZ (4.0–13.9 pM) than the SAFZ (1.2–5.1 pM), which may be partly attributed to stimulated siderophore production by environmental factors such as dust‐derived iron concentrations (up to 0.51 nM). Multiple types of siderophores were identified on both cruises, including ferrioxamines, amphibactins, and iron‐free forms of photoreactive siderophores, which suggest active production and use of diverse siderophores across latitude and depth. Siderophore biosynthesis and uptake genes and transcripts were widespread across latitude, and higher abundances of these genes and transcripts at higher latitudes may reflect active siderophore‐mediated iron uptake by the local bacterial community across the North Pacific. The variability in the taxonomic composition of bacterial communities that transcribe putative ferrioxamine, amphibactin, and salmochelin transporter genes at different latitudes further suggests that the microbial groups involved in active siderophore production and usage change depending on local conditions.

Glycine betaine uptake and metabolism in marine microbial communities - Angela K. Boysen; Bryndan P. Durham; William Kumler; Rebecca S. Key; Katherine R. Heal; Laura T. Carlson; Ryan D. Groussman; E. Virginia Armbrust; Anitra E. Ingalls (Environmental Microbiology, 2022)
Summary Glycine betaine (GBT) is a compatible solute in high concentrations in marine microorganisms. As a component of labile organic matter, GBT has complex biochemical potential as a substrate for microbial use that is unconstrained in the environment. Here we determine the uptake kinetics and metabolic fate of GBT in two natural microbial communities in the North Pacific characterized by different nitrate concentrations. Dissolved GBT had maximum uptake rates of 0.36 and 0.56 nM h −1 with half‐saturation constants of 79 and 11 nM in the high nitrate and low nitrate stations respectively. During multiday incubations, most GBT taken into cells was retained as a compatible solute. Stable isotopes derived from the added GBT were also observed in other metabolites, including choline, carnitine and sarcosine, suggesting that GBT was used for biosynthesis and for catabolism to pyruvate and ammonium. Where nitrate was scarce, GBT was primarily metabolized via demethylation to glycine. Gene transcript data were consistent with SAR11 using GBT as a source of methyl groups to fuel the methionine cycle. Where nitrate concentrations were higher, more GBT was partitioned for lipid biosynthesis by both bacteria and eukaryotic phytoplankton. Our data highlight unexpected metabolic pathways and potential routes of microbial metabolite exchange.

Physical activity in relation to circulating hormone concentrations in 117,100 men in UK Biobank - Eleanor L. Watts; Aurora Perez-Cornago; Aiden Doherty; Naomi E. Allen; Georgina K. Fensom; Sandar Tin Tin; Timothy J. Key; Ruth C. Travis (Cancer Causes & Control, 2021)
Purpose Physical activity may reduce the risk of some types of cancer in men. Biological mechanisms may involve changes in hormone concentrations; however, this relationship is not well established. Therefore, we aimed to investigate the associations of physical activity with circulating insulin-like growth factor-I (IGF-I), sex hormone-binding globulin (SHBG, which modifies sex hormone activity), and total and free testosterone concentrations, and the extent these associations might be mediated by body mass index (BMI). Methods Circulating concentrations of these hormones and anthropometric measurements and self-reported physical activity data were available for 117,100 healthy male UK Biobank participants at recruitment. Objectively measured accelerometer physical activity levels were also collected on average 5.7 years after recruitment in 28,000 men. Geometric means of hormone concentrations were estimated using multivariable-adjusted analysis of variance, with and without adjustment for BMI. Results The associations between physical activity and hormones were modest and similar for objectively measured (accelerometer) and self-reported physical activity. Compared to men with the lowest objectively measured physical activity, men with high physical activity levels had 14% and 8% higher concentrations of SHBG and total testosterone, respectively, and these differences were attenuated to 6% and 3% following adjustment for BMI. Conclusion Our results suggest that the associations of physical activity with the hormones investigated are, at most, modest; and following adjustment for BMI, the small associations with SHBG and total testosterone were largely attenuated. Therefore, it is unlikely that changes in these circulating hormones explain the associations of physical activity with risk of cancer either independently or via BMI.

Multi-stressor Effects of Ultraviolet Light, Temperature, and Salinity on Louisiana Sweet Crude Oil Toxicity in Larval Estuarine Organisms - Marie E. DeLorenzo; Peter B. Key; Katy W. Chung; Kaitlin Aaby; Deanna Hausman; Cheldina Jean; Paul L. Pennington; Emily C. Pisarski; Edward F. Wirth (Archives of Environmental Contamination and Toxicology, 2021)

Uptake and Biological Effects of Perfluorooctane Sulfonate Exposure in the Adult Eastern Oyster Crassostrea virginica - Allisan A. Aquilina-Beck; Jessica L. Reiner; Katy W. Chung; Meaghan J. DeLise; Peter B. Key; Marie E. DeLorenzo (Archives of Environmental Contamination and Toxicology, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Patterns and trends in lead (Pb) concentrations in bald eagle (Haliaeetus leucocephalus) nestlings from the western Great Lakes region - Jason E. Bruggeman; William T. Route; Patrick T. Redig; Rebecca L. Key (Ecotoxicology, 2018)

Toxicity comparison of the shoreline cleaners Accell Clean® and PES-51® in two life stages of the grass shrimp, Palaemonetes pugio - Sarah-Marie E. Baxter; Marie E. DeLorenzo; Peter B. Key; Katy W. Chung; Emily Pisarski; Barbara Beckingham; Michael H. Fulton (Environmental Science and Pollution Research, 2018)

Comparative Toxicity of Two Chemical Dispersants and Dispersed Oil in Estuarine Organisms - M. E. DeLorenzo; P. B. Key; K. W. Chung; E. Pisarski; B. Shaddrix; E. F. Wirth; P. L. Pennington; J. Wade; M. Franco; M. H. Fulton (Archives of Environmental Contamination and Toxicology, 2018)

Effects of salinity on oil dispersant toxicity in the eastern mud snail, Ilyanassa obsoleta - Marie E. DeLorenzo; Brittany N. Evans; Katy W. Chung; Peter B. Key; Michael H. Fulton (Environmental Science and Pollution Research, 2017)

Dietary greenhouse gas emissions of meat-eaters, fish-eaters, vegetarians and vegans in the UK - Peter Scarborough; Paul N. Appleby; Anja Mizdrak; Adam D. M. Briggs; Ruth C. Travis; Kathryn E. Bradbury; Timothy J. Key (Climatic Change, 2014)

Interactive Effects of Mosquito Control Insecticide Toxicity, Hypoxia, and Increased Carbon Dioxide on Larval and Juvenile Eastern Oysters and Hard Clams - R. N. Garcia; K. W. Chung; P. B. Key; L. E. Burnett; L. D. Coen; M. E. DeLorenzo (Archives of Environmental Contamination and Toxicology, 2014)

Physical activity, sex steroid, and growth factor concentrations in pre- and post-menopausal women: a cross-sectional study within the EPIC cohort - S. Rinaldi; R. Kaaks; C. M. Friedenreich; T. J. Key; R. Travis; C. Biessy; N. Slimani; K. Overvad; J. N. Østergaard; A. Tjønneland; A. Olsen; S. Mesrine; et al. (Cancer Causes & Control, 2014)

Marine atmospheric boundary layer over some Southern Ocean fronts during the IPY BGH 2008 cruise - C. Messager; S. Speich; E. Key (Ocean Science, 2012)
A set of meteorological instruments was added to an oceanographic cruise crossing the Southern Ocean from Cape Town to 57°33' S during the summer of 2008. The Cape Cauldron, the Subtropical, Subantarctic, Polar and southern Antarctic Circumpolar current fronts were successively crossed. The recorded data permitted to derive the exchange of momentum, heat and water vapour at the ocean-atmosphere interface. A set of 38 radiosonde releases complemented the dataset. The marine atmospheric boundary layer characteristics and air-sea interaction when the ship crossed the fronts and eddies are discussed. The specific role of the atmospheric synoptic systems advection on the air-sea interaction over these regions is highlighted. Additionally, the Subantarctic front mesoscale variability induced an anticyclonic eddy considered as part of the Subantarctic front. The specific influence of this Agulhas ring on the aloft atmosphere is also presented.

Prediagnostic concentrations of plasma genistein and prostate cancer risk in 1,605 men with prostate cancer and 1,697 matched control participants in EPIC - Ruth C. Travis; Naomi E. Allen; Paul N. Appleby; Alison Price; Rudolf Kaaks; Jenny Chang-Claude; Heiner Boeing; Krasimira Aleksandrova; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; J. Ramón Quirós; et al. (Cancer Causes & Control, 2012)

Detecting post-fire burn severity and vegetation recovery using multitemporal remote sensing spectral indices and field-collected composite burn index data in a ponderosa pine forest - Xuexia Chen; James E. Vogelmann; Matthew Rollins; Donald Ohlen; Carl H. Key; Limin Yang; Chengquan Huang; Hua Shi (International Journal of Remote Sensing, 2011)

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

Erratum to: Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2011)

Menopausal hormone therapy and risk of ovarian cancer in the European prospective investigation into cancer and nutrition - Konstantinos K. Tsilidis; Naomi E. Allen; Timothy J. Key; Laure Dossus; Rudolf Kaaks; Kjersti Bakken; Eiliv Lund; Agnès Fournier; Christina C. Dahm; Kim Overvad; Louise Hansen; Anne Tjønneland; et al. (Cancer Causes & Control, 2011)

Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2010)

Prospective study of physical activity and risk of primary adenocarcinomas of the oesophagus and stomach in the EPIC (European Prospective Investigation into Cancer and nutrition) cohort - José María Huerta; Carmen Navarro; María-Dolores Chirlaque; María-José Tormo; Karen Steindorf; Genevieve Buckland; Fátima Carneiro; Nina Føns Johnsen; Kim Overvad; Jakob Stegger; Anne Tjønneland; Marie-Christine Boutron-Ruault; et al. (Cancer Causes & Control, 2010)

Fruits and vegetables consumption and the risk of histological subtypes of lung cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) - F. L. Büchner; H. B. Bueno-de-Mesquita; J. Linseisen; H. C. Boshuizen; L. A. L. M. Kiemeney; M. M. Ros; K. Overvad; L. Hansen; A. Tjonneland; O. Raaschou-Nielsen; F. Clavel-Chapelon; M.-C. Boutron-Ruault; et al. (Cancer Causes & Control, 2010)

Effects of chemically spiked sediments on estuarine benthic communities: a controlled mesocosm study - W. L. Balthis; J. L. Hyland; M. H. Fulton; P. L. Pennington; C. Cooksey; P. B. Key; M. E. DeLorenzo; E. F. Wirth (Environmental Monitoring and Assessment, 2010)

Lifestyle factors and serum androgens among 636 middle aged men from seven countries in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Reiko Suzuki; Naomi E. Allen; Paul N. Appleby; Timothy J. Key; Laure Dossus; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; Carlotta Sacerdote; Domenico Palli; Vittorio Krogh; Rosario Tumino; et al. (Cancer Causes & Control, 2009)

Lifestyle factors and serum androgens among 636 middle aged men from seven countries in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Reiko Suzuki; Naomi E. Allen; Paul N. Appleby; Timothy J. Key; Laure Dossus; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; Carlotta Sacerdote; Domenico Palli; Vittorio Krogh; Rosario Tumino; et al. (Cancer Causes & Control, 2009)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Fruit and vegetable consumption and lymphoma risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Sabine Rohrmann; Nikolaus Becker; Jakob Linseisen; Alexandra Nieters; Thomas Rüdiger; Ole Raaschou-Nielsen; Anne Tjønneland; Hans E. Johnsen; Kim Overvad; Rudolf Kaaks; Manuela M. Bergmann; Heiner Boeing; et al. (Cancer Causes & Control, 2007)

An evaluation of contaminated estuarine sites using sediment quality guidelines and ecological assessment methodologies - M. Fulton; P. Key; E. Wirth; A. K. Leight; J. Daugomah; D. Bearden; S. Sivertsen; G. Scott (Ecotoxicology, 2006)

Relationship of alcohol intake and sex steroid concentrations in blood in pre- and post-menopausal women: the European Prospective Investigation into Cancer and Nutrition - S. Rinaldi; P. H. M. Peeters; I. D. Bezemer; L. Dossus; C. Biessy; C. Sacerdote; F. Berrino; S. Panico; D. Palli; R. Tumino; K. T. Khaw; S. Bingham; et al. (Cancer Causes & Control, 2006)

A prospective study of diet and prostate cancer in Japanese men - Naomi E. Allen; Catherine Sauvaget; Andrew W. Roddam; Paul Appleby; Jun Nagano; Gen Suzuki; Timothy J. Key; Kojiro Koyama (Cancer Causes & Control, 2004)

Surface Water Pesticide Movement from the Dade County Agricultural Area to the Everglades and Florida Bay via the C-111 Canal - M. H. Fulton; G. I. Scott; M. E. DeLorenzo; P. B. Key; D. W. Bearden; E. D. Strozier; C. J. Madden (Bulletin of Environmental Contamination and Toxicology, 2004)

Toxicity of the Insecticides Fipronil and Endosulfan to Selected Life Stages of the Grass Shrimp ( Palaemonetes pugio ) - P. B. Key; K. W. Chung; A. D. Opatkiewicz; E. F. Wirth; M. H. Fulton (Bulletin of Environmental Contamination and Toxicology, 2003)

Lifestyle determinants of serum insulin-like growth-factor-I (IGF-I), C-peptide and hormone binding protein levels in British women - Naomi E. Allen; Paul N. Appleby; Rudolf Kaaks; Sabina Rinaldi; Gwyneth K. Davey; Timothy J. Key (Cancer Causes & Control, 2003)

Lifestyle and nutritional determinants of bioavailable androgens and related hormones in British men - Naomi E. Allen; Paul N. Appleby; Gwyneth K. Davey; Timothy J. Key (Cancer Causes & Control, 2002)

Microsatellite markers for investigating population structure in Octopus vulgaris (Mollusca: Cephalopoda) - E. C. Greatorex; C. S. Jones; J. Murphy; L. N. Key; A. M. Emery; P. R. Boyle (Molecular Ecology, 2000)

Toxicity of Sediment Associated PAHs to the Estuarine Crustaceans, Palaemonetes pugio and Amphiascus tenuiremis - E. F. Wirth *, M. H. Fulton; G. T. Chandler; P. B. Key; G. I. Scott (Bulletin of Environmental Contamination and Toxicology, 1998)

In Situ Monitoring of Dredged Material Spoil Sites Using the Oyster Crassostrea virginica - E. F. Wirth; G. I. Scott; M. H. Fulton; R. F. Van Dolah, P. P. Maier, N. Hadle; P. B. Key (Archives of Environmental Contamination and Toxicology, 1996)

In situ monitoring of dredged material spoil sites using the oyster Crassostrea virginica - E. F. Wirth; G. I. Scott; M. H. Fulton; R. F. Van Dolah; P. P. Maier; N. Hadley; J. W. Daugomah; P. B. Key (Archives of Environmental Contamination and Toxicology, 1996)

Primary irritant contact dermatitis from synthetic pyrethroid insecticide exposure - Stephen A. Flannigan; Stephen B. Tucker; Marcus M. Key; Charles E. Ross; Edward J. Fairchild; Barbara A. Grimes; Ronald B. Harrist (Archives of Toxicology, 1985)